The effect of organic dust exposure on long-term change in lung function: a systematic review and meta-analysis. Issue 7 (12th April 2017) - Bolund, Anneli CS; Miller, Martin R; Sigsgaard, Torben; Schlünssen, Vivi
Abstract : Lung function is a predictor of morbidity and mortality, and the chronic nature of lung function decline allows for preventive initiatives. Proinflammatory constituents of organic dust are considered a possible cause of compromised respiratory health. The aim of this systematic review was to reveal the impact of organic dust exposure on long-term change in lung function. The literature search was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. Predefined criteria concerned study design: longitudinal, ≥1 year follow-up, ≥50 exposed; exposure measures: organic dust, measured or estimated, in different occupational settings; and outcome measures: change in lung function measured by spirometry. Based on these criteria, 1580 potentially relevant publications were narrowed down to 20 included publications. Quality was evaluated and discussed based on six objectively defined criteria. Overall, 14 studies found some type of association between exposure to organic dust and long-term change in lung function. However, the results were inconsistent and no specific work exposure showed more clear associations to change in lung function. Meta-analysis revealed an overall small significant excess loss in forced expiratory volume in the 1st s for exposed compared with controls of 4.92 mL/year (95% CI 0.14 to 9.69). No significant association was seen overall for forced vital capacity. 12 studies revealed a significant exposure–response relation between organic dust and change in lung function. The results were inconsistent across varying study design and different exposure measures and outcomes. We therefore conclude that there is limited evidence of a causal association between general exposure to organic dust and long-term excess decline in lung function.